2023
DOI: 10.3390/pharmaceutics15010246
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Targeted Nanocarriers for the Management of Triple Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is a life-threatening form of breast cancer which has been found to account for 15% of all the subtypes of breast cancer. Currently available treatments are significantly less effective in TNBC management because of several factors such as poor bioavailability, low specificity, multidrug resistance, poor cellular uptake, and unwanted side effects being the major ones. As a rapidly growing field, nano-therapeutics offers promising alternatives for breast cancer treatment. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 243 publications
0
7
0
Order By: Relevance
“…The core of the NPs was made up of siRNA–protamine complex, and the shell contained an aptamer ligand for targeting CD44 expressed on TNBC cells. The outcome of the study indicated that the formulation targeting TNBC cells demonstrated enhanced anticancer effects [ 168 , 169 ].…”
Section: Potential Applications Of Precision-medicine Therapy For Tnbcmentioning
confidence: 99%
“…The core of the NPs was made up of siRNA–protamine complex, and the shell contained an aptamer ligand for targeting CD44 expressed on TNBC cells. The outcome of the study indicated that the formulation targeting TNBC cells demonstrated enhanced anticancer effects [ 168 , 169 ].…”
Section: Potential Applications Of Precision-medicine Therapy For Tnbcmentioning
confidence: 99%
“…TNBC is a prominent cause of cancer deaths in women due to its aggressive nature and a lack of effective therapy methods (Berger et al 2021;Akter et al 2023). Studies have shown that TNBC formation and occurrence involved abnormally active mitogen-activated protein kinase/extracellular signal-regulated kinases (MAPK/ERK), which may provide TNBC the capacity to multiply and withstand apoptosis (Kim et al 2016;Ryu and Sohn 2021;Pradhan et al 2023;Yang et al 2023a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The siRNA drug was formulated with cationic lipid-assisted PEG-PLA NPs to target cyclin-dependent kinase 1 for TNBC therapy. The NPs inhibited c-myc overexpressing TNBC cells by reducing CDK-1 expression [ 64 , 65 ]. Further, aptamer-guided siRNA NPs targeting CD44 expression in TNBC were prepared [ 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…The NPs inhibited c-myc overexpressing TNBC cells by reducing CDK-1 expression [ 64 , 65 ]. Further, aptamer-guided siRNA NPs targeting CD44 expression in TNBC were prepared [ 65 ]. The results of the study demonstrated that the drug exhibited improved anticancer effects against TNBC [ 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%